(untitled) (Journal of Nematode Morphology and Systematics, 2010)
Bursaphelenchus africanus sp. n. isolated from packaging wood made of Pinus radiata and imported from the Republic of South Africa to China is described. It is characterized by a body length of 723 (638-803) μm and 828 (701-956) μm of males and females, respectively; slim body (a = 34 and 33, resp.); stylet 15 μm long; lateral field with four lines; mean value of vulva position 77%; appearance of a vulval flap in lateral view; length of postuterine branch about two-thirds of the vulva-anus distance; female tail long and conical (c = 17), tapering to a finely rounded terminus; male with spicules 22 μm long having only weakly developed rostrum and condylus, and cross-striped in their central part; male tail terminus with distinct bursa seen in dorso-ventral position; three pairs of ventro-sublateral papillae (one pair preanal, two pairs postanal just in front of the bursa and adjacent to each other) and a single preanal papilla present. The combination of four lateral lines and the position of caudal papillae reveal a relationship of the new species to other four-lined groups (‘xylophilus’ group, ‘fungivorus’ group); however, the shape of the spicules is different and unique among the known species of Bursaphelenchus. The delimitation from the ‘xylophilus’group and the ‘fungivorus’ group is shown by sequencing results. This is the second Bursaphelenchus species known to occur in South Africa.